A mixed-methods national study investigating key challenges in learning English as a foreign language: A Chinese college student perspective - Huang, Jinyan; Li, Junfei; Shu, Tiantian; Zhang, Yongfang (Frontiers in Psychology, 2022)
This mixed-methods national study of “Chinese college students’ challenges, strategies, and metacognitive self-assessment (MSA) in English as a foreign language (EFL) learning” examined 1,525 Chinese college students’ key challenges, coping strategies, and MSA practice and perceived benefits in EFL learning. The instrument was a survey that consisted of a five-point Likert scale self-evaluation form and three essay questions addressing their key challenges, coping strategies, and MSA practice, respectively. This article only reported the findings on their key challenges. The quantitative results indicated that listening, speaking, and writing were their three key difficult areas in EFL learning; further, students’ subject discipline (arts versus sciences verse English subject disciplines) had significant effects on their perceived learning challenges in English listening and vocabulary. The qualitative results confirmed that listening, speaking, and writing were their three key challenging areas. Their specific learning challenges in each area were examined. Implications for Chinese college English teachers and administrators are discussed in terms of pedagogy and policy making, respectively.